Education Supervision in Increasing Competence Teachers in Curriculum 2013 (Study of Education Management Analysis) - Bahdin Nur Tanjung (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
Administrators must be transferred to ensure quality learning. That is, that the success of the implementation of supervision is measured by increasing student learning achievement. Tenriningsih (2009) believes that there is a positive and significant direct relationship between master's performance and positive and significant achievement between student achievements through teaching administrators". This means that the higher the master's performance. The higher the student's learning achievement is then to produce the necessary teacher supervision effective for teaching. Supervision of education develops along with the development of management science. At the beginning of its development, supervision was carried out using an inspection approach. Supervisor comes to school and observes the teaching of the teacher. The focus of the supervisor's attention is to find teachers' mistakes based on work standards formulated in such a way by the education authority. The teacher carries out the task in accordance with standard operational procedures. Supervisors with teachers are two parties as subordinate superiors. Supervisors have a higher level of truth. The research method by the author uses the systematic method Literature Review (SLR), by gathering several sources of information from journals, books and other articles. To improve the source of reading that will be produced by the reader later. Then after the sources are collected, the new author can conclude what results have been obtained from this reading source.